Assessment of Adolescents in Child-to-Parent Violence: Invariance, Prevalence, and Reasons - Luis Burgos-Benavides; M. Carmen Cano-Lozano; Andrés Ramírez; Samuel P. León; Venus Medina-Maldonado; Francisco Javier Rodríguez-Díaz (MDPI AG, 2024)
Child-to-parent violence is a form of family violence where the children are the aggressors. Objective: This study first aimed to analyze the psychometric validity of the Child-to-Parent Violence Questionnaire (CPV-Q) among Ecuadorian adolescents. Second, the measurement invariance across the children's sex was examined. Finally, the prevalence of child-to-parent violence (CPV) was also determined. Methods: A total of 2084 adolescents aged 12 to 18 years participated in this study. The participants were residents of two provinces in southern Ecuador. A higher percentage of participants were women. They lived mostly with their father and mother. The married marital status of the parents was the most frequently reported. Most of the fathers and mothers of the participants completed primary education. The sampling design was probabilistic, with proportional allocation by age and quotas according to the number of inhabitants per province. The sample size was determined by using a finite population formula. All the participants were randomly selected. The CPV-Q was used to assess child-to-parent violence. The items were adapted linguistically and tailored to the Ecuadorian context. Results: The questionnaire demonstrated excellent model fit and adequate reliability. Full measurement invariance was held for all scales except for the reasons subscale pertaining to fathers. Statistically significant differences were observed with respect to the sex of the aggressor, with control/domain behaviors toward both parents and psychological violence toward the mother being more frequent among daughters than sons. Similarly, reactive reasons were more frequent among daughters than sons. Conclusion: This study provides significant psychometric evidence on the CPV-Q in Ecuadorian adolescents along with data on the prevalence of violence against parents.